Reappraisal of hepatocellular adenoma from Federal Health System, Rio de Janeiro, Brazil - Vidoti, Danielle Basta Delai (2019)
Background: Hepatocellular adenoma is a rare liver tumor that may require surgical treatment in cases of hemorrhage or suspicion of malignant lesions. Aim: To analyze data from patients who underwent hepatectomy for hepatocellular adenoma (HCA) in Rio de Janeiro, Brazil. Methods: From January 2005 to March 2019, sixty-nine patients with HCA underwent hepatectomy at centers in Rio de Janeiro. They were included in the analysis patients undergoing hepatectomy with pathological diagnosis of hepatocellular adenoma and excluded patients with hepatectomy with anatomopathological diagnosis other than hepatocellular adenoma, mainly nodular focal hyperplasia. Data related to patients, tumor and surgery were analyzed retrospectively. Results: Sixty patients (87%) were female and nine were male. Among women, 83% had a history of contraceptive use; among men, only one had an androgen intake history. Overall mean age was 36.4 years (15 - 49), with men older than women (33.9 ± 8.14 years vs. 40.4 ± 6.27 years; P = 0.02). Forty one patients reported abdominal pain, associated or not to other symptoms; 32% had an episode of hemorrhage; 28 were asymptomatic with an incidental radiological finding. In total, 45 patients presented only one lesion and overall mean size was 8.1 cm (2 - 31); tumors were larger among men (mean size 12.9 ± 9.86 cm vs. 7.7 ± 4.58 cm; P = 0.009). Twenty one surgeries were laparoscopic. Hepatocellular carcinoma (HCC) was identified in three specimens and the incidence was higher among men (22.2% vs. 1.6%; P = 0.042) and in tumors larger than 20 cm (66.6% vs. 0.02%). There was no perioperative mortality. Two of the three patients with HCC died with extrahepatic recurrence; the remaining patient is well after 36 months. Overall mean follow-up time was 14.2 months (2 - 76). Conclusion: Male patients with HCA were older and had larger tumors when compared to females. Incidence of HCC was higher among men and in lesions larger than 20 cm. Male patients with HCA should be treated more aggressively than females.